A survey of Public Relations techniques of selected Public Libraries in Metro Manila - Cabrera, Ma. Christina C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1994)
The public library is an institution dependent upon the good opinion of the population it serves for its prosperity and usefulness. It is common knowledge that Filipinos are lacking in awareness of our public libraries, their collections and services. This study's purpose is to discover how these libraries promote themselves and how effective their public relations program are.
This research study aims to: (1) inquire into the state of the public relations programs of the following libraries: Manila City Libraries, Makati Municipal Library, Pasig Library and Museum and Quezon City Public Library; (2) discover what are the public relations techniques being employed by these libraries; and (3) know how effective are their public relations techniques.
This study hypothesizes that: there is a significant relationship between the kind of public relation techniques used in our public libraries and the turnout of library clientele.
The study follows the methodology of survey research design. The subjects are the professional library personnel in charge of the library promotion and a random sampling of clientele from each of the four libraries. Questionnaires are the main instrument used.
Data gathered from the four respondent libraries have revealed that three out of the four public libraries included in the survey have an active, well-defined public relations program. Basically, there are fourteen public relations techniques which the one or the other libraries use in promoting the libraries' image. They are: 1) news release or press release; 2) library publications; 3)booklists; 4) library guides and handbooks; 5) annual reports; 6) library newsletters; 7) library posters, billboards, slogans; 8) exhibits and displays; 9) public service announcements; 10) "Friends of the library"; 11)presentations to community groups; 12) library programs; 13) personal publicity; and 14) National Library Week programs.
According to the data gathered, the librarians themselves feel that their public relations program are still lacking in some areas. The lack of funds is a major factor why the Pasig Library and Museum does not have an established public relations program. In truth, only the Makati Municipal Library set aside a portion of their budget for the purpose of public relations.
The researcher therefore concludes that at the moment, the public relations program of our public libraries are not yet well developed. There is still something missing in the programs surveyed in this study. For one thing, the majority of the public who are making use of our public libraries seem to come only from one part of the society. The libraries has not yet managed to attract the attention of people from all walks of life. The kind of public relations campaign of a library should depend on two things: 1) the library's resources and facilities; and 2) the library's clientele.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Manila Metropolitan Area; Public relations -- Libraries -- Philippines -- Manila Metropolitan Area